Methicillin-resistant Staphylococcus aureus nasal carriage among patients receiving hemodialysis in Taiwan: prevalence rate, molecular characterization and de-colonization - Kang, Yu-Chuan (BioMed Central, 2012)
BACKGROUND: Staphylococcus aureus, particularly methicillin resistant (MRSA), is a common pathogen among patients receiving hemodialysis. To evaluate nasal carriage, molecular characterization and effectiveness of decolonization of MRSA among patients receiving hemodialysis in Taiwan, we conducted this study. METHODS: From January to June 2011, two nasal samplings with a 3-month interval were obtained from patients undergoing hemodialysis in a medical center (CGMH), and in a local hospital (YMH) and sent for detection of MRSA. For MRSA carriers, decolonization procedures were administered. All patients in CGMH were observed if MRSA infections occurred during the study period. RESULTS: A total of 529 nasal specimens (265 from CGMH and 264 from YMH) were collected from 296 patients (161 from CGMH and 135 from YMH). 233 patients participated in both surveys. Average one-time point MRSA carriage rate was 3.8%, and the rate was up to 6.9% for those with two-time point surveys. No additional significant factor for MRSA carriage was identified. Seventy percent of the 20 colonizing MRSA isolates, though categorized as healthcare-associated strains epidemiologically, shared common molecular characteristics of the local community-associated strains. Only one of the 20 MRSA-colonized patients failed decolonization and had persistent colonization, while without any intervention, 17 (61%) of 28 patients with methicillin-sensitive S. aureus colonization in the first survey had persistent colonization of a genetically indistinguishable strain. Within the study period, two patients (1.24%) in CGMH, one with MRSA colonization (9.1%), developed MRSA infection. CONCLUSION: A substantial proportion of patients receiving hemodialysis in Taiwan had MRSA colonization, mostly genetically community strains. Decolonization procedures may effectively eliminate MRSA colonization and might reduce subsequent MRSA infection in these patients.